Relative age effect in Spanish Karate Championships - Lorenzo-Couso, R.; Martinez de Quel, O. (Revista de Artes Marciales Asiaticas, 2016)
Some voices in karate are asking for grouping athletes into categories with a cutoff based on the year of birth, from January to December, instead of the current system where groups are based on the age at the day of the championship. These voices could be ignoring the possible importance of the relative age effect (RAE). RAE has been studied in many sports (Wattie, Schorer, & Baker, 2015). In those where athletes are grouped by year of birth it has proved to be born in the early months of the year (January-March) is an advantage. When the division is done by season from August to July, those born between August and October would have the advantage (Barnsley, Thompson, & Legault, 1992). This effect is relevant in children competition because of their maturation and development, but it remains until adult categories due to the lack of opportunities given to athletes born in the last months of the year. Thus, nowadays, professional sport institutions are concerned about the loss of talent because of RAE and some precautions are being taken in order to make a better and fairer distribution of this advantage. In karate, it is usual to divide age categories based on the age of athletes at the day of the championship. Therefore, it is supposed that general advantage is not for those born in the first quarter of the year but this is distributed throughout the four quarters. Nevertheless, for a specific championship, the advantage would be for older athletes in each age category. The aim of this study was to explore the relative age effect in the Spanish Karate Championships.